Infrastructure Projects as a Sustainable Tool for Ukraine's Recovery and Development: A Bibliometric Perspective - Tverezovska, Oleksandra; Subačienė, Rasa; Hrytsenko, Larysa (Buhalterinės apskaitos teorija ir praktika, 2024)
In the current realities of a full-scale war, economic, political, and environmental crises in Ukraine, the issue of post-war recovery and further sustainable economic development is of paramount importance. The path to sustainable recovery depends significantly on the end of the war, successful implementation of infrastructure projects, and continued international support. However, any process should begin with a thorough analysis of its theoretical implications and a comprehensive evaluation of its concept. The aim of the research is to investigate the evolution of research on “infrastructure projects” within the context of sustainable development. Research methods involve bibliometric analysis, data extraction, keyword analysis, network analysis, and data visualization. The article explores the theoretical principles of infrastructure projects as a driver for the sustainable development of Ukraine. Within the scope of this research, a bibliometric analysis of the essence of the terms “infrastructure project” and "sustainable infrastructure project” was conducted. It revealed a dynamic evolution in the scholarly discourse surrounding “infrastructure projects”. While the term “infrastructure project” has been present in academic literature since 1979, a significant surge in research activity is evident from the early 2000s onwards. This surge reflects a growing recognition of the critical role infrastructure plays in economic and social development, alongside the escalating concerns surrounding environmental sustainability and climate change. The emergence and rapid growth of research on “sustainable infrastructure projects” is a notable trend. This indicates a relatively recent but rapidly evolving area of scholarly inquiry, reflecting the increasing emphasis on environmental, social, and economic sustainability in infrastructure development. These findings provide a foundation for understanding the evolving discourse on sustainable infrastructure and its potential role in Ukraine's post-war recovery.
Keywords: bibliometric analysis; infrastructure project; sustainable infrastructure project; sustainable development